The role of prostate-specific membrane antigen positron emission tomography in detecting recurrence in patients with biochemical relapse after primary radiotherapy for localised prostate cancer: a systematic review and meta-analysis - Omar Alghazo; Thomas Milton; Kate Wilson; Mrunal Hiwase; Michael S. Hofman; Matthew Hong; Alex Jay; Michael O’Callaghan (Clinical and Translational Imaging, 2026)
Abstract Objective To evaluate the diagnostic efficacy of prostate-specific membrane antigen positron emission tomography–computed tomography (PSMA PET–CT) in detecting and localising recurrence in patients with biochemical relapse (BCR) following definitive radiotherapy for prostate cancer. Methods A systematic review and meta-analysis was conducted according to PRISMA guidelines. Comprehensive searches of Ovid MEDLINE, Ovid Embase, and the Cochrane Library identified studies reporting PSMA PET–CT findings in patients with rising PSA after external beam radiotherapy or brachytherapy. Twenty-one studies involving 2925 patients met inclusion criteria. Pooled detection rates and recurrence patterns were analysed using a random-effects model. Subgroup analyses were performed according to PSA level. Results PSMA PET–CT demonstrated a high pooled detection rate of 90% (95% CI 87–91%) for recurrence after radiotherapy. Detection remained high at 77% (95% CI 72–81%) in patients with PSA < 2 ng/ml. PSMA PET–CT localised recurrence to the prostate or pelvic lymph nodes in 54% of cases and identified distant metastases in 46%. In this low-PSA subgroup, recurrence was predominantly localised to the prostate or pelvic lymph nodes (72%), underscoring the potential for earlier, targeted salvage treatment. Conclusions PSMA PET–CT provides high diagnostic accuracy for detecting recurrent prostate cancer post-radiotherapy, including in patients with PSA levels below the Phoenix threshold. Its ability to accurately localise recurrence supports its growing role in guiding personalised salvage treatment strategies.